PENGARUH KECERDASAN LOGIS-MATEMATIS TERHADAP HASIL BELAJAR IPA SISWA KELAS VI DI SD NEGERI 10 KOTA BANDA ACEH - Fauzi Fauzi.; Monawati Monawati. (Jurnal Pesona Dasar, 2019)
This study aims to determine the effect of logical-mathematical intelligence on science learning outcomes of sixth-grade students at SD Negeri 10 Banda Aceh. This study used a quantitative approach with a type of associative research. The samples in this study were 28 of sixth-grade students consisting of 14 male students and 14 female students. Samples were taken using cluster sampling. Data collection using tests was conducted to measure logical-mathematical intelligence and documentation of science learning outcomes. The data analysis technique used was a simple regression analysis. The data was processed using f-test statistics with a significant level of α = 0.05 using SPSS ver. 23, the results obtained as much as 20.2% were influenced by logical-mathematical intelligence and 79.8% were influenced by other factors. Therefore the result obtained was  thus Ho was rejected and Ha was accepted. It could be concluded that there was a significant influence between logical-mathematical intelligence on science learning outcomes of sixth-grade students at SD Negeri 10 Banda Aceh.